New geometrid moths from Iraqi Kurdistan (Lepidoptera, Geometridae: Sterrhinae, Larentiinae) - Khudhur, Farhad A.; Hausmann, Axel (Zootaxa, 2024)
A large number of geometrid moths was collected by the first author in Iraqi Kurdistan including several undescribed species and subspecies. In this paper we describe three new geometrid taxa: Idaea medianocturna walaila ssp. nov., Lulavia mahwii sp. nov. and Protorhoe drechseli nebuloides ssp. nov. We present differential diagnoses and images of adult moths and genitalia.